Linux bible - Negus, Christopher 1957- (Wiley, 2020)
The industry favorite Linux guideLinux Bible, 10th Edition is the ultimate hands-on Linux user guide, whether you're a true beginner or a more advanced user navigating recent changes. this updated tenth edition covers the latest versions of Red Hat Enterprise Linux (RHEL 8), Fedora 30, and Ubuntu 18.04 LTS. It includes information on cloud computing, with new guidance on containerization, Ansible automation, and Kubernetes and OpenShift. With a focus on RHEL 8, this new edition teaches techniques for managing storage, users, and security, while emphasizing simplified administrative techniques with Cockpit. Written by a Red Hat expert, this book provides the clear explanations and step-by-step instructions that demystify Linux and bring the new features seamlessly into your workflow.This useful guide assumes a base of little or no Linux knowledge, and takes you step by step through what you need to know to get the job done.* Get Linux up and running quickly* Master basic operations and tackle more advanced tasks* Get up to date on the recent changes to Linux server system management* Bring Linux to the cloud using Openstack and Cloudforms* Simplified Linux administration through the Cockpit Web Interface* Automated Linux Deployment with Ansible* Learn to navigate Linux with Amazon (AWS), Google (GCE), and Microsofr Azure Cloud servicesLinux Bible, 10th Edition is the one resource you need, and provides the hands-on training that gets you on track in a flash
The ultimate guide to mastering LinuxThis fully updated 10th edition of Linux Bible gives beginners and intermediate users alike the knowledge and skills to take Linux to the next level. With an emphasis on command-line tools and a focus on the latest versions of Red Hat Enterprise Linux, Fedora, and Ubuntu, renowned Linux expert and bestselling author Christopher Negus guides you step-by-step through detailed demonstrations and exercises designed to provide you with a thorough understanding and working knowledge of the Linux operating system. Linux Bible, 10th Edition also provides exam prep materials for various Linux certifications.Linux is at the heart of most technological advances in cloud computing and that means you need a solid understanding of Linux to work effectively in tomorrow's data centers. . - The Linux basics you learn early on in the book are applied in later chapters as the author demonstrates how to deploy Linux systems as hypervisors, cloud controllers, and virtual machines, as well as manage virtual networks and networked storage.Linux Bible, 10th Edition shows you how to get and install Linux, begin using it, and ultimately excel at administering and securing it. . - This book is also an excellent resource for software developers who wish to use Linux as a developer workstation.The Linux Bible, 10th Edition shows you how to:* Get started with Linux* Implement data center automation with Ansible* Access a shell and write simple shell scripts* Simplify system administration with Cockpit* Secure Linux systems and networks* Configure various servers and troubleshoot common problems* Create Linux virtual machines that run on hypervisors and cloud platforms* Learn containerization with Docker and Podman, including container orchestration with Kubernetes and OpenShiftStart with any Linux system and advance to enterprise Linux computing* Use your favorite Linux distribution to learn and test your skills with Linux command-line tools* Learn pro
Acknowledgments xi; Introduction xxxv; Part I: Getting Started 1; Chapter 1: Starting with Linux 3; Chapter 2: Creating the Perfect Linux Desktop 27; Part II: Becoming a Linux Power User 59; Chapter 3: Using the Shell 61; Chapter 4: Moving Around the Filesystem 93; Chapter 5: Working with Text Files 113; Chapter 6: Managing Running Processes 131; Chapter 7: Writing Simple Shell Scripts 147; Part III: Becoming a Linux System Administrator 165; Chapter 8: Learning System Administration 167; Chapter 9: Installing Linux 195; Chapter 10: Getting and Managing Software 221; Chapter 11: Managing User Accounts 249; Chapter 12: Managing Disks and Filesystems 273; Part IV: Becoming a Linux Server Administrator 305; Chapter 13: Understanding Server Administration 307; Chapter 14: Administering Networking 339; Chapter 15: Starting and Stopping Services 369; Chapter 16: Configuring a Print Server 403; Chapter 17: Configuring a Web Server 427; Chapter 18: Configuring an FTP Server 455; Chapter 19: Configuring a Windows File Sharing (Samba) Server 475; Chapter 20: Configuring an NFS File Server 499; Chapter 21: Troubleshooting Linux 523; Part V: Learning Linux Security Techniques 563; Chapter 22: Understanding Basic Linux Security 565; Chapter 23: Understanding Advanced Linux Security 599; Chapter 24: Enhancing Linux Security with SELinux 635; Chapter 25: Securing Linux on a Network 663; Part VI: Engaging with Cloud Computing 691; Chapter 26: Shifting to Clouds and Containers 693; Chapter 27: Using Linux for Cloud Computing 709; Chapter 28: Deploying Linux to the Cloud 729; Chapter 29: Automating Apps and Infrastructure with Ansible 749; Chapter 30: Deploying Applications as Containers with Kubernetes 765; Part VII: Appendixes 785; Appendix A: Media 787; Appendix B: Exercise Answers 797; Index 863
Keywords: LINUX; Betriebssysteme, Benutzeroberflächen